Effect of Nonionic Surfactant on the Micro‐Emulsifying Water in Silicone Media. Issue 1 (27th October 2016) - Pei, Liujun; Wu, Ping; Liu, Juanjuan; Wang, Jiping
Abstract: Reverse micro‐emulsion dyeing technology shows a high dye uptake and fixation rate, and effectively decreases the amount of waste water in the textile industry. However, the influence of surfactants and co‐surfactants on micro‐emulsifying water in reverse micro‐emulsions has not been investigated. In this study, the micro‐emulsifying mechanism in silicone media and the influence of nonionic surfactants and co‐surfactants on micro‐emulsifying water have been investigated. The results show that a large amount of water can be emulsified using alcohol‐polyoxyethylene ethers, especially under 3–5 ethylene oxide groups in molecular structure. As co‐surfactant, alcohol which contains 4–9 carbon chains could spontaneously form reverse micro‐emulsions in silicone media. The effects of solution pH and ionic strength on the amount of emulsified water were also evaluated. The results show that a large amount of water could be emulsified in silicone media at solution pH 2–9. Meanwhile, the amount of emulsified water decreased with increasing ionic strength. Thus, the optimum conditions for water emulsification are low ionic strength and pH between 2 and 9.